2016
DOI: 10.4172/2165-8056.1000139
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Pharmacological Mushroom: Pleurotus eryngii

Abstract: Pleurotus eryngii, commonly known as the king oyster mushroom, has been used extensively in North Africa, Europe and Asia. A great deal of work has been carried out on therapeutic potential of Pleurotus eryngii. The edible Fungi perform multiple bioactivities: anticancer, antiviral, antioxidant, antimicrobial, anti-leukaemia, hypolipidemic, immuno-modulating and estrogen-like activity. These bioactive properties depend on its bioactive compounds such as polysaccharides, eryngiolide A, ubiquinone-9, pentacyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…levels. The potential lactogenic effect of polysaccharide extracts from P. eryngii has been reported in a few studies [44,46,47]. Our results demonstrated that P. eryngii mushrooms from both substrates induced a significant increase of lactobacilli compared to NC and baseline after 24-h fermentation, showing an analogous effect to the prebiotic inulin.…”
Section: Discussionsupporting
confidence: 79%
“…levels. The potential lactogenic effect of polysaccharide extracts from P. eryngii has been reported in a few studies [44,46,47]. Our results demonstrated that P. eryngii mushrooms from both substrates induced a significant increase of lactobacilli compared to NC and baseline after 24-h fermentation, showing an analogous effect to the prebiotic inulin.…”
Section: Discussionsupporting
confidence: 79%
“…Three cerebrosides with different lengths of the fatty acid portion have been isolated and identified from Pleurotus cornucopiae (Paulet) Rolland (Lee et al 2017). Furthermore, purified acidic glycosphingolipids (AGLs) from P. eryngii were reported to induce interleukin-2 (IL-2) release from invariant natural killer T (iNKT) cells inducing prolonged retention of IL-4 in serum in vitro and in vivo (Fu et al 2016). So through iNKT cell activation AGLs isolated from P. eryngii might be involved in the maintenance of immunohomeostasis.…”
Section: Fatty Acids and Lipidsmentioning
confidence: 99%
“…6)-Dglucosyl residues side chains. They showed a strong inhibitory effect on lipid accumulation (Fu et al 2016). Recently, a mannogalactan with the main chain of (1 ?…”
Section: Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The king oyster mushroom (Pleurotus eryngii) is a well-known edible macro mushroom cultivated all over the world and has been reported to possess various pharmacological benefits to human health [1]. The bioactive constituents of P. eryngii have been intensively investigated in recent years.…”
Section: Introductionmentioning
confidence: 99%